Impact of food advertising in social media among local university students in Malaysia - Tan, Ai Ling *; Loo, Poh Theng (Australian Academy of Business and Social Sciences, 2014)
Malaysia is well-known for its multi-cultural people and foods. With the emerging on the social media, it influences the food choice decision among Malaysian Consumers especially the university students who are technology savvy. There are many studies on food advertising, but so far limited studies have been conducted to understand the impacts of social media in food advertising among local university students in Malaysia. Therefore, the aim of this paper is to examine the overall attitude and behavioral intention of local university students toward food advertising in social media (e.g. Facebook, Twitter, Blogs). 231 samples were recruited with convenient sampling method. With the findings, it can help the academicians and industry practitioners to have better understanding on attributes of food advertising in social media that contribute significantly to students’ food purchase decision.